The Effect of Dry Land Governance in Madura Island in Islamic Perspective - Mohammad Nasih (Institute of Advanced Scientific Research, Inc., 2019)
The objectives of this study was to test and analyze the influence of exogenous variables Dry Land Management on indigenous variables Agricultural Productivity of Dry Land and Absorbed Workforce and People's Welfare in Madura Island in Islamic perspective. The test analysis tools used is Kasyf/Intuitive analysis, integrated Sharia qualitative with Smart-Partial Least Square, then the abstract can be compiled as below: Dry Land Governance has a positive and significant effect on Agricultural Productivity of Dry Land but has a positive and insignificant effect on Absorbed Workforce, it also has a negative and significant effect on People's Welfare in Madura Island. Whereas the Absorbed Workforce has a negative and insignificant effect on Agricultural Productivity of Dry Land and has a negative and insignificant effect on People's Welfare in Madura Island. The result of the study proves the enactment of the law of diminishing return, where the total of Absorbed Workforce is increasing but the productivity is decreasing. This study also proves that the multidisciplinary and dynamic modification model of Ibn Khladun has been applied to the activity of dry land agriculture in Madura Island, along with that, Zadjuli theory about line of poverty and prosperity can be applied to measure the level of welfare in Madura Island, so it can be said that Dry Land Governance is not yet kaffa according to Islamic law. Based on the intuitive or kasyf analysis, proved that Dry Land Governance in Madura Island has been unsuitable to Koran Al A'raf verse 56-57 but the low rainfall level in Madura Island as the shadow of rainfall in East Java mainland is suitable to Koran Al Baqarah verse 265. © 2019 Jour of Adv Research in Dynamical and Control Systems. All rights reserved.